Assessment of medical students in the final obstetrics and gynaecology clinical examination (MBBS): Comparing the Objective Structured Clinical Examination (OSCE) using (MAM) and the Traditional Long Obstetric Case (TOC) - Mohamed Ahmed A (Global Journal of Medicine and Public Health, 2015)
Background For many years, the traditional long obstetric case (LOC) remains the standard clinical examination in obstetrics and gynaecology in the majority of medical schools in the world. Because it has so many shortcomings, a move towards the (OSCE) took place. The objective of this study was to assess the performance of the students in the final clinical examination in obstetrics and gynaecology (MBBS) comparing OSCE using (MAM) as standard setting method to determine the cut off score, and the (LOC). Methods The current comparative study was conducted in the National Ribat University, Khartoum. One hundred and three students were examined by the (OSCE) in 10 stations. The cut score was determined by the (MAM). We took also the (50%) as a fixed cut off score for the (OSCE) examination. On the other hand, we took the performance of 103 students who were examined by the (LOC) in the previous batch. A comparison then was made about the performance of the students. Funding—none GJMEDPH 2015; Vol. 4, issue 5 1Department of Obstetrics and Gynaecology, Faculty of Medicine, The National Ribat University, Khartoum, Sudan 2Department of Community Medicine, College of Medicine, Majmaah University, Saudi Arabia *Corresponding Author: Elsadig Yousif Mohamed Department of Community Medicine, College of Medicine, Majmaah University, Saudi Arabia ey.mohamed@mu.edu.sa Telephone Number: 00966530748432 Conflict of Interest—none Results The performance of the students in the (LOC) and the (OSCE) when the cut score was decided by (MAM) was: 91(88.4%) passed in the (LOC) and 85(82.5%) passed in the (OSCE). The performance of the students in the (LOC) and the (OSCE) when the cut score for the (OSCE) was taken as (50%) was: 91(88.4%) passed in the (LOC) and 94(91.3%) in the (OSCE). Conclusion There was no significant difference in the number of the students who passed/failed the clinical examination between the (OSCE) using (MAM) to determine the cut off score and the (LOC), the (LOC) and the (OSCE) when the cut off score was taken as (50%). The (MAM) can be used in clinical examination as an item referenced standard setting method to determine the cut off score.